A retrospective observational study of the effectiveness of long acting antipsychotic injectable on hospital admissions - Charles, Bhaskaran Nathamaniar (Department of Psychiatry and Mental Health, 2019)
Background: The impact on hospitalisations/ relapse rates of utilising long-acting antipsychotic injectable (LAIs) in a South African population suffering from chronic psychotic spectrum mental illness is poorly researched. Aim: To compare the duration and number of hospitalisation episodes 12 and 24 months before and after the initiation of a LAI. Setting: Valkenberg Hospital’s adult acute inpatient psychiatry services. Method: This was a retrospective naturalistic observational mirror-image study. Hospitalisation was utilised as a proxy for relapse. Results: Sixty-one patients were identified for the study. A comparison of the 12 months before LAI initiation to the 12 months following LAI initiation showed a reduction in the number of admissions of 44% (55 to 31), and a reduction in the number of inpatient days of 23% (1892 to 1464). There was a statistically significant reduction in the median number of hospital admissions (p = 0.005) and median inpatient days (p = 0.040). Comparing the 24 months before to the 24 months following LAI initiation, there was a reduction in the number of admissions of 30% (91 to 64) and inpatient days of 4% (3477 to 3355). There was a statistically significant reduction in the median number of hospital admissions (p = 0.014) and a non-statistically significant reduction in median days (p = 0.428). Conclusion: The prescription of a LAI reduced the duration and number of hospital admissions over a 12-month period. After 24 months, there were fewer admissions but no significant reduction in the number of inpatient days. This study supports findings of international mirror-image studies.